Students’ genre expectations and the effects of text cohesion on reading comprehension - Schmitz, Anke; Gräsel, Cornelia; Rothstein, Björn (Reading & writing, 2017)
This study raises the question what makes school texts comprehensible by analyzing whether students’ genre expectations about literary or expository texts moderate the impact of different forms of text cohesion on reading comprehension, even when the texts are similar regarding their genre. 754 students (Grade 9) from comprehensive schools read one of four text versions with similar content, but different degrees of local and global text cohesion. The four more or less cohesive texts were introduced as literary texts (part of a story) or as expository texts (newspaper article), although the different genres were only purported and the texts contained both literary and expository passages. Reading comprehension was assessed with multiple-choice-items, semi-open, and open-ended questions. Results demonstrate that global cohesion was profitable for reading comprehension with expository expectations, but not with literary ones. Local text cohesion and both forms of cohesion in combination did not interact with students’ genre expectations and had no main effect on comprehension. When students reading skills and prior knowledge were considered, the interaction was still apparent. Moreover, students with lower levels of reading skills tended to profit especially from texts with global cohesion, whereas the readers with higher reading skills achieved equal means in reading comprehension irrespective of the degree of global text cohesion. The findings are discussed with respect to theoretical aspects of text–reader-interactions, cognitive and emotional components of genre expectations, and the composition and instruction of comprehensible school texts.